PHRASEOLOGICAL REDUCTION AS A STAGE OF EXPRESSIVE DERIVATION (USING THE EXAMPLE OF PHRASEOLOGICAL NEOLOGISM NA KRAINYAK) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-32-44The lexical and phraseological level of the language system is constantly in dynamics, reflecting the communicative needs of society. Changes in the socio-political life of recent decades have also caused a change in the attitude of native speakers of modern Russian to the language norm. The boundary between codified and uncodified speech is not always clear. This determines the active interaction of colloquial and slang speech. The increased expressiveness of oral speech causes people who use urban slang to need to transform the linguistic means they know, entailing their reduction and increasing the expressiveness of the utterance. Such processes contribute to the use of phraseological units as a means of expressive derivation. However, a free transition from communication involving slang units to communication within the framework of literary and colloquial speech can ensure that some of the reduced phraseological neologisms enter the circle of colloquial units, and then it is possible to continue the derivation process, as a result of which the language system can be enriched with a new lexical unit. Using the example of the phraseological neologism “na krainyak” (to the extreme), one can see the mechanism of action of phraseological reduction as an intermediate stage of expressive derivation.Key words: expressive derivation, uncodified speech, phraseological neologism, phraseological reduction